'At home it's just so much easier to be yourself': older adults' perceptions of ageing in place. Issue 3 (1st December 2014) - STONES, DAMIEN; GULLIFER, JUDITH
ABSTRACT: By 2050, the number of people in Australia aged over 85 is expected to quadruple. Yet, from a socio-psychological research perspective, little is known about the experiences of people who continue to live at home during late old age (85 years and over), a period when challenging problems associated with ageing escalate and threaten to compromise independence. Utilising a qualitative methodology, the subjective lived experience of 23 very old adults (19 women, four men, with a mean age of 90.7 years, range 85–101 years) who live independently in rural Australia were elicited. The aims of the research were to understand their thoughts and feelings about ageing in place at home, and what psychological, social and practical adaptive strategies they employ to cope with difficulties encountered during very old age. In-depth interviews were analysed in an interpretive phenomenological tradition of thematic analysis, interpretation of paradigm cases and interpretation of exemplars. Participants described how historical, cultural and environmental contexts shaped their everyday thoughts, activities and what was meaningful for them. The findings add to our understanding of the largely unnarrated lives of the very old, suggest a need for person-centred home-care assessment processes and aid significant others (family, friends and neighbours) to understand better what very old adults need to live independently.